Prinsip Manajemen Pemasaran dalam Islam - Sarja (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
To achieve a company’s succes or maintain business continuity it must have a vision and mission of the company and be carried out by looking at the present and future living conditions, to be used as healthy business opportunities to compate. No less important in the success of the company’s vision and mission targets is a marketing effort that continues to be developed and innovated because the level of competition in the business world is running tight. In this case, islamic marketing management has a strategic position, therefore this islamic marketing is based on the qur’an and the sunnah of the prophet Muhammad. Which becomes asource in various businesses of a muslim in his business is always looking for two advantages, namely world profits and the benefist of the hablum minAllah (relationship with God) and hablum minannas (human relations), and protect nature and the enveironment.